RELIGIOSITY OF THE CHARACTERS IN NOVEL API TAUHID BY HABIBURRAHMAN EL SHIRAZY (A SEMIOTIC STUDY) - Hayati, Nurul; Darmahusni, (IJLECR (International Journal of Language Education and Cultural Review), 2018)
The objective of this research was to understand comprehensively about religiosity of the characters in novel Api Tauhid by Habiburrahman El Shirazy based on a semiotic study. It was a qualitative research with content analysis method. The data were collected through literature study, observed matters related to the religiosity of the characters in novel Api Tauhid by Habiburrahman El Shirazy. The data analysis and interpretation include semiotic studies use the theory of Pierce seen from the dimensions of faith, Islam, and ihsan(virtue). The sense of faith can be seen from unity of God, Islam can be seen from the worship performed by the characters, and ihsan can be seen from the behavior and deeds of the characters. This research is expected to be useful in the process of learning language and literature, especially in the use of semiotic methods to facilitate students to understand literature and language.